2015
DOI: 10.1098/rsif.2014.1394
|View full text |Cite
|
Sign up to set email alerts
|

Transitional flow in aneurysms and the computation of haemodynamic parameters

Abstract: Haemodynamic forces appear to play an influential role in the evolution of aneurysms. This has led to numerous studies, usually based on computational fluid dynamics. Their focus is predominantly on the wall shear stress (WSS) and associated derived parameters, attempting to find correlations between particular patterns of haemodynamic indices and regions subjected to disease formation and progression. The indices are generally determined by integration of flow properties over a single cardiac cycle. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…We have assumed rigid walls similar to previous simulations [2, 14, 17, 19] because the displacement of aneurysm's wall is typically small and the flow patterns of small distensible and rigid models in the carotid region are very similar [32]. In addition, we have assumed Newtonian fluid in our simulations because the non-Newtonian effects are negligible in larger (>500  μ m) arteries [33] and previous simulations of both Newtonian and non-Newtonian fluids have shown similar flow patterns [19].…”
Section: Governing Equations and The Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have assumed rigid walls similar to previous simulations [2, 14, 17, 19] because the displacement of aneurysm's wall is typically small and the flow patterns of small distensible and rigid models in the carotid region are very similar [32]. In addition, we have assumed Newtonian fluid in our simulations because the non-Newtonian effects are negligible in larger (>500  μ m) arteries [33] and previous simulations of both Newtonian and non-Newtonian fluids have shown similar flow patterns [19].…”
Section: Governing Equations and The Numerical Methodsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) holds an important position in the investigation of hemodynamic factors in aneurysms because of its higher resolution near the walls relative to experimental methods such as laser Doppler velocimetry, particle image velocimetry, and magnetic resonance imaging, which is required to compute hemodynamic factors such as shear stress correctly [8, 9]. Many investigations have been carried out on the hemodynamics of IAs using experimental methods [1012] and CFD [7, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The effect of WSS divergence on WSSET can become important in higher Reynolds numbers where the WSS divergence can become very high. In the present study, we only used one cardiac cycle of WSS data and assumed periodicity to generate WSS trajectories, although cycle-to-cycle variations in WSS exist in some cardiovascular flows such as AAAs [46]. However, our aim in this study was to demonstrate the applicability of our approach and comparison to existing methods.…”
Section: P 10mentioning
confidence: 99%
“…[5,35,36]). However, in light of a recent study by Poelma et al [54], we investigated the statistical convergence of these variables, as it had become clear that the systolic pulses were creating fluctuations within the CIAA that continued through diastole. When similar behaviour was present in a model of Poelma et al [54], they showed that 28 cycles of data did not lead to complete convergence at a particular location.…”
Section: Tawss Osi and Ecapmentioning
confidence: 99%
“…With this in mind, we approximated the blood flow as laminar and considered the blood to be an incompressible fluid with a density of 1050 kg/m 3 . The walls of the arteries were characterised by no-slip, rigid wall boundary conditions [5,6,32,35,54,55] and the viscosity was modelled using a non-Newtonian approximation (Carreau-Yasuda, as implemented by Biasetti et al [44]; [56]). By using a non-Newtonian model, as opposed Newtonian, we can capture the macro-scale shear-thinning of the blood, allowing a one-way Lagrangian particle transport model to provide a good prediction of individual blood-cell trajectories within the continuous phase (blood).…”
Section: Physical Assumptions and Boundary Conditionsmentioning
confidence: 99%